Artificial Intelligence’s impact on Marketing - bento; Lopes da Costa, R.; Pereira, L.; Gonçalves, R.; Dias, Á. (VI International Forum on Management – Familia y tecnología: Factores de resiliencia de las PYMEs durante la pandemia, 2022)
Today’s business environment reinforces digitalization, a phenomenon particularly noticeable with the Covid-19 pandemic. Companies must survive a fast-moving and constantly changing business environment, an increasingly fierce competition, and increasingly exigent customers. To differentiate themselves from the competitors many companies chose to adopt “new” technologies. Companies are introducing Artificial Intelligence as a way to be innovative and improve their strategies. Research deems Marketing as the main beneficiary of this technology. This reserach’s main objective is to examine Artificial Intelligence’s Impact on Marketing, understanding the extent of the introduction of this technology in companies located in Portugal, comprehend whether they use it on Marketing and explore the results of this decision. To do so, the research used a qualitative approach, the content analysis of twenty-one interviews with professionals familiar with the theme. Concluding that even though the majority of the interviewees introduced Artificial Intelligence, a big part of them does not use it in a continuous manner. When assessing the interviewees’ perception of this technology, only one did not considered it to be a competitive advantage. According to the interviewees, the main challenge is the cost of the investment, and the benefit is the strategic information the system produces. The interviewees stated that the key change is emergence of Marketing 1to1 (due to the levels of personalization achieved), allowing companies to offer a better customer experience, resulting in the increase of customer satisfaction, which, consequently, translates itself in the increase of customer loyalty.